The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/978-3-319-51691-2_31
|View full text |Cite
|
Sign up to set email alerts
|

Binary PSO for Web Service Location-Allocation

Abstract: Web services are independent programmable application components which scatter over the Internet. Due to the improvement on local computing power and development on high-speed Internet, network latency has a significant impact on determining the service response time. Thus, physical locations of web services and users should be taken into account for web service composition. In this paper, we propose a new solution based on the binary PSO-based approach to allocate the service locations. Although several heuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…For now, the problem model considers each service as an atomic service. With the increasing usages of composite services composed with atomic services distributed over the Internet [46], [47], we need to consider service composition workflow while solving WSLAP. Service composition workflows have a significant impact on the allocation of atomic services because the data flow between services could not be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…For now, the problem model considers each service as an atomic service. With the increasing usages of composite services composed with atomic services distributed over the Internet [46], [47], we need to consider service composition workflow while solving WSLAP. Service composition workflows have a significant impact on the allocation of atomic services because the data flow between services could not be neglected.…”
Section: Discussionmentioning
confidence: 99%
“… 2021 ), gate matrix layout (de Oliveira and Lorena 2002 ), web service location-allocation (Tan et al. 2017 ), water distribution system (Zheng et al. 2014 ), oil well drilling (Guria et al.…”
Section: Binary Metaheuristic Algorithms In Applicationsmentioning
confidence: 99%
“…Tan et al suggested an improved binary PSO algorithm which uses adaptive inertia technology to assign web service locations (Tan et al. 2017 ). Figure 6 presents its binary encoding, and indicates whether service s is allocated at position j .…”
Section: Binary Metaheuristic Algorithms In Applicationsmentioning
confidence: 99%
“…Based on the analysis, Liu et al [97] proposed a BPSO algorithm named Up BPSO, which outperformed the standard BPSO algorithm with a constant and a linearly decreasing inertia weight. Up BPSO was already applied to achieve web-service allocation [98], which aimed to minimize network latency and cost to deploy servers.…”
Section: Binary Pso (Bpso)mentioning
confidence: 99%